PELATIHAN MENULIS KREATIF BAGI PELAJAR MA DI KABUPATEN JOMBANG - Mariana Ulfah Hoesny; Umi Anis Roisatin; Henny Purwaningsih; Achmad Sjaifullah; Abdul Muqit (JPM PAMBUDI, 2022)
The advance of technology and the emergence of Industrial Revolution 4.0 have initiated many applications that are based on internet. One of examples is online platform for reading and writing. Today, printed books have reduced its popularity due to the development of online reading and writing platforms as well as electronic books. In regard with this, creative writing skill has become important since it can encourage people, in this case students to learn to write so they can be more creative and critical in thinking. In addition, they can also gain some money. This PPM activity is aimed at conducting a training on creative writing to provide students with basic skills of creative writing. Webinar dan training were used as methods to reach the targeted goals. The results of the webinar showed that students realize the importance of creative writing both as skill that support them in language learning as well as in real life.